The Influence of Leadership and Work Discipline on Employee Performance Mediated by Employee Work Motivation at the Poasia District Village Office: Leadership - Harnisa Harnisa; Murdjani Kamaluddin; Rince Tambunan (Oikonomia : Journal of Management Economics and Accounting, 2025)
This study aims to find out and analyze (1) The influence of leadership on employee work motivation in the Poasia District Village Office; (2) The influence of leadership on employee performance at the Poasia District Village Office; (3) The effect of work discipline on employee work motivation at the Poasia District Village Office; (4) The effect of work discipline on employee performance at the Poasia District Village Office; (5) The effect of work motivation on employee performance at the Poasia District Village Office; (6) The influence of leadership on employee performance is mediated by employee work motivation at the Poasia District Village Office; and (7) The influence of work discipline on employee performance is mediated by employee work motivation at the Poasia District Village Office. The determination of the number of samples in this study is by using the census method, namely the number of samples taken from the total population of 33 employees consisting of 8 people from the Poasia District office, 5 people from Anduonohu Village, 5 people from Rahandouna Village, 5 people from Anggoeya Village, 5 people from Matabubu Village, and 5 people from Wundumbatu Village. The data analysis technique in this study uses Partial Least Square (PLS). Based on the results of the study, it can be concluded that (1) Leadership has a positive and significant effect on the work motivation of employees at the Poasia District Village Office; (2) Leadership has a positive and significant effect on the performance of employees at the Poasia District Village Office; (3) Work discipline has a positive and significant effect on the work motivation of employees at the Poasia District Village Office; (4) Work discipline has a positive and significant effect on employee performance at the Poasia District Village Office; (5) Work motivation has a positive and significant effect on employee performance at the Poasia District Village Office; (6) Leadership has a positive and significant effect on employee performance through employee motivation at the Poasia District Village Office; (7) Work discipline has a positive and significant effect on employee performance through employee work motivation at the Poasia District Village Office.